2013
DOI: 10.1167/iovs.13-12946
|View full text |Cite
|
Sign up to set email alerts
|

Neural Crest Origin of Retinal and Choroidal Pericytes

Abstract: Since YFP-positive PCs and vSMCs are colocalized with NG2 and PDGFRβ, we propose that capillary PCs and vSMCs in the retina and the optic nerve, both parts of the central nervous system, as well as in the choroid, a tissue of mesodermal origin, derive from the neural crest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 59 publications
3
73
0
1
Order By: Relevance
“…To date, contribution of neural crest cells to brain MCs has been demonstrated in vertebrates including mice, bird and zebrafish (Etchevers et al, 2001;Heglind et al, 2005;Korn et al, 2002;Trost et al, 2013;Wang et al, 2014;Yamanishi et al, 2012). In agreement with this, our analyses indicated a neural crest origin of MCs in the anterior part of the brain and in the hyaloid vessels.…”
Section: Discussionsupporting
confidence: 89%
“…To date, contribution of neural crest cells to brain MCs has been demonstrated in vertebrates including mice, bird and zebrafish (Etchevers et al, 2001;Heglind et al, 2005;Korn et al, 2002;Trost et al, 2013;Wang et al, 2014;Yamanishi et al, 2012). In agreement with this, our analyses indicated a neural crest origin of MCs in the anterior part of the brain and in the hyaloid vessels.…”
Section: Discussionsupporting
confidence: 89%
“…It is possible that these cells are glia that are not in immediate contact with neural processes, given prior reports of heterogeneous glial cells in the enteric nervous system that varied in expression of traditional glial markers, morphology and location in the intestinal wall (Boesmans et al, 2015). However, others have reported that vascular pericytes in the thymus, retina, and choroid derive from neural crest based on studies using Cre lineage tracing (Trost et al, 2013; Zachariah and Cyster, 2010). The nature and function of the rare Sox10+ vascular-associated cells we observe in the bladder wall remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…6 In contrast, Sox10 is expressed in both neural crest and other non-neural crest lineages, such as oligodendrocytes and inner ear, during development, 7, 9 and its expression continues in later development and adult tissues, mainly in the central and peripheral nervous systems, 10 which was demonstrated by several reporter mouse lines, such as Sox10-rtTA, 11 Sox10-Venus, 12 Sox10-Cre 13 and Sox10-CreER 14 . Studies on vascular development using Sox10-Cre/CreER mice showed that Sox10+ cells differentiated into pericytes and SMCs in the brain, 14 eye, 15 thymus, 16, 17 ascending aorta, aorta arch, carotid arteries 13 , and the neural crest origin of these cells were verified by the studies on quail-chick chimera or Wnt1-Cre mice. 35, 16, 18 In addition, the study on Wnt1-Cre mice also showed that neural crest cells give rise to SMCs of coronary arteries in the heart, 18 although there is no such report from Sox10-Cre mice.…”
mentioning
confidence: 90%